Peran Orang Tua dalam Memotivasi Belajar Siswa - 'Aisyatinnaba', Nur; Sutoyo, Anwar (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
The purpose of research to find out how the role of parents in motivating students. This research is a case study. The research was conducted in class VIII SMP Negeri 3 Sejong Bradford, with subject five students and five parents. Methods of data collection using scale of motivation to learn and interview. Data analysis using qualitative descriptive data. The results showed, subjects one, have a high learning motivation, high parental role in motivating learning. The subject of two has a low learning motivation, poor parental role in motivating student learning. Subjects of three, have moderate learning motivation, the role of parents is in motivating learning. The subject of four has a high learning motivation, high parental role in motivating learning. Five subjects, show low learning motivation, low parental role in motivating learning. So concluded the role of parents in motivating learning the subject one and four high, medium and subject three subjects two and five low.